Genetic and Environmental Contributions of Negative Valence Systems to Internalizing Pathways. (25th January 2018) - Cecilione, Jennifer L.; Rappaport, Lance M.; Hahn, Shannon E.; Anderson, Audrey E.; Hazlett, Laura E.; Burchett, Jason R.; Moore, Ashlee A.; Savage, Jeanne E.; Hettema, John M.; Roberson-Nay, Roxann
Abstract : The genetic and environmental contributions of negative valence systems (NVS) to internalizing pathways study (also referred to as the Adolescent and Young Adult Twin Study) was designed to examine varying constructs of the NVS as they relate to the development of internalizing disorders from a genetically informed perspective. The goal of this study was to evaluate genetic and environmental contributions to potential psychiatric endophenotypes that contribute to internalizing psychopathology by studying adolescent and young adult twins longitudinally over a 2-year period. This report details the sample characteristics, study design, and methodology of this study. The first wave of data collection (i.e., time 1) is complete; the 2-year follow-up (i.e., time 2) is currently underway. A total of 430 twin pairs ( N = 860 individual twins; 166 monozygotic pairs; 57.2% female) and 422 parents or legal guardians participated at time 1. Twin participants completed self-report surveys and participated in experimental paradigms to assess processes within the NVS. Additionally, parents completed surveys to report on themselves and their twin children. Findings from this study will help clarify the genetic and environmental influences of the NVS and their association with internalizing risk. The goal of this line of research is to develop methods for early internalizing disorder risk detection.